Study Perkembangan Perekonomian Jambi Masa Hindia-Belanda (1906-1942) Sebagai Bahan Ajar Pembelajaran Sejarah Berbasis Lokal: Indonesia - Seprina, Reka (Jurusan Pendidikan IPS FKIP UNJA, 2021)
Jambi is one of the areas that can not be separated from the cultivation of Dutch colonialism in 1906-1942 (36 years), this brought changes in Jambi in the field of political system, brings in Jambi in the field of political, socio-cultural and economic systems. This research was conducted to identify how the economic development of western influences, especially Dutch Colonialism in Jambi, can be used as a source of learning, especially teaching materials based on local history in Jambi, especially during the period of colonialism and Dutch imperialism. This research method uses qualitative descriptive research. The results showed that the economic development of Jambi during Colonialism can be used as a teaching material for local history in the subjects of Indonesian History and The History of Interest. This locally based teaching material is very useful for learners because the material is close to the environment of life, thus making the goal of historical learning achieved and become more meaningful. In addition, it can also build a character of love for history and the nature of responsibility for preservation, concern for heritage and historical relics and the growth of nationalism.